Antimicrobial Resistance of Campylobacter jejuni Isolated from Chicken in Nakhon Pathom Province, Thailand - Jananya Sukhapesna; Patamaporn Amavisit; Worawidh Wajjwalku; Arinthip Thamchaipenet; Thavajchai Sukpuaram (Agriculture and Natural Resources, 2005)
Campylobacter jejuni isolated from retail market-chicken in Nakhon Pathom province were determined for resistance to quinolone and other antimicrobial agents by broth microdilution method. Sixty-eight C. jejuni strains were resistant to quinolone drugs including nalidixic acid (69.12%), norfloxacin (69.12%), ciprofloxacin (58.82%) and marbofloxacin (25.00%). High proportions of the isolates were resistant to tetracycline (77.94%), sulfamethoxazole (72.06%), kanamycin (51.47%), ampicillin 47.06% and streptomycin (42.65%). Low proportions of the isolates were found resistance to gentamycin (16.18%) and erythromycin (13.23%). Nearly 97% of the isolates were multiple resistances to more than 4 antimicrobial agents tested.